The problem of military security in the modern Russian-Norwegian relations - N. A. Flegontov (Проблемы постсоветского пространства, 2024)
The article analyzes security issues in the relations between Russia and Norway in 2000–2022. The relevance of the topic is attributed to the importance of Norway for the Russian foreign policy, the significant role of Norway in the Arctic, as well as the current militarization with the increasing influence of external actors on regional military security. The purpose of the study is to assess the changing role of military security in the bilateral relations. When it comes to the methodology, the author relies on the methods of comparative and critical analysis, content analysis, historical method, and a systematic approach. The plan of the research includes an analysis of Norway’s strategic position and the factors behind its approach to maintaining national and regional security; fundamentals of Russia’s military activities in the Russian Arctic zone; the reasons and significance of strengthening Russia’s military potential in the Arctic; bilateral cooperation in the military sphere. The author notes that Norwegian military planning is largely determined by NATO policy and the Alliance’s relations with Russia. Amid the aggravation of the dialogue between Russia and the collective West after The Five-Day War in Georgia, and the escalation of the Ukrainian conflict, Russia became perceived by the Norwegian authorities as a threat to national security. The change in the Norwegian approach, in particular, expressed in the desire to strengthen the role of NATO in the region, led to the curtailment of all programs of military cooperation with Russia and provoked the strengthening of the Russian military presence in the Arctic. In conclusion, the author notes that, despite the rather developed military cooperation until 2014, amid the global security crisis, a return to the pre-crisis level of mutual understanding in the military sphere is unlikely.